PENGARUH BRAND AMBASSADOR AKTOR KOREA TERHADAP NIAT BELI KONSUMEN PADA SKINCARE INDONESIA DI KUPANG - Pramanenda Sinaga, Mentari Putri; Y. Sahetapy, Stella; Adi, Johan Constantino (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract A brand ambassador must be the representation of image and identity of a brand. They tend to build costumers’ trust to the product in order to create buying transactions. Recently, there are some local skincare brands who hired korean male celebrities to be the face of their products. This phenomenon belongs to a discourse that is engaging to study, since they have brighter skin then Indonesian especially people who come from East of Indonesia. This study aims to investigate the meaning of visual presentation of the brand ambassador on five advertisements and define the customers’ purchase intention. To interprete the advertisements, the authors apply Kress and Van Leewen’s (2006) visual grammar. The authors also conduct a survey to women respondents that will be proceed quantitatively with SPSS 27. Kewywords: Purchase Intention, Brand Ambassador, Visual Grammar, Advertisment, Discourse. Abstrak Seorang duta merek (Brand Ambassador) harus menjadi representasi citra dan identitas merek. Mereka cenderung membangun kepercayaan pelanggan terhadap produk untuk menciptakan transaksi pembelian. Baru-baru ini, beberapa merek perawatan kulit lokal mempekerjakan selebriti pria Korea sebagai wajah produk mereka. Fenomena ini termasuk dalam suatu wacana yang menarik untuk dipelajari, karena mereka memiliki kulit yang lebih cerah daripada orang Indonesia, terutama orang yang berasal dari Timur Indonesia. Penelitian ini bertujuan untuk menyelidiki makna presentasi visual duta merek pada tiga iklan dan menentukan niat beli pelanggan. Untuk menginterpretasi iklan, penulis menerapkan tata bahasa visual Kress dan Van Leewen (2006). Penulis juga melakukan survei kepada responden wanita yang akan diproses secara kuantitatif menggunakan SPSS 27. Kata Kunci: Niat Beli, Duta Merek, Tata Bahasa Visual, Iklan, Wacana.